(untitled) (Research, Society and Development, 2024)
Introduction: Acute viral bronchiolitis (AVB) is determined as the first episode of wheezing in children under 24 months. The main agent is the respiratory syncytial virus, responsible for the high hospitalization rates. Among the main risk factors are age, prematurity, Cardiopathies and most importantly, Down Syndrome. This genetic condition increases vulnerability in respiratory infections, resulting from abnormality in the immune system and airways. To reduce hospitalization rates, Palivizumab, an antibody that inhibits the entry and replication of RSV in high-risk individuals, is used. Objective: To evaluate whether the use of Palivizumab in patients with Down syndrome reduces the risk and/or length of hospitalization for AVB. Methodology: This is an integrative review, researching on PubMed, BVS and Cochrane Library databases, containing articles from the last 10 years that include premature children under 2 years and with Down Syndrome. Results: Seven papers were selected from 67 publications. Conclusion: The prophylactic Palivizumab in patients with Down Syndrome shows a reduction in RSV hospitalizations. However, there are gaps in the data in other aspects such as the length of hospitalization, need for supplemental oxygen, time in the ICU and mechanical ventilation. Therefore more research is needed to address these points.